Entrepreneurship Content Learning to Improve Student Well-Being in Vocational Education - Astuti, Widya Puji; Hernawan, Asep Herry; Dewi, Laksmi (Universitas Negeri Semarang, 2025)
Entrepreneurship content learning in vocational education plays a strategic role in addressing the persistent issue of low student well-being in Indonesia. Well-being represents a multidimensional construct that includes psychological resilience, social integration, and financial independence, all of which are essential for preparing students to enter the labor market with confidence. The study employed a qualitative approach with a prospective case study design conducted in the Tourism Department of SMKN 1 Pacet, Cianjur, during September 2024. Data were collected through participatory observation, semi-structured interviews, and documentation of entrepreneurial learning activities. Findings demonstrated that entrepreneurship content learning strengthened psychological well-being by increasing self-confidence, motivation, and adaptability. Social well-being was enhanced through improved collaboration, empathy, and communication skills, while financial well-being developed through students’ ability to apply entrepreneurial knowledge in generating income. The conclusion confirms that entrepreneurship content learning contributes significantly to advancing vocational education by simultaneously fostering employability skills and promoting comprehensive student well-being. The contribution of the study lies in providing empirical evidence that entrepreneurship-oriented curricula support not only professional competence but also sustainable educational development.